Religious Identity Construction in Transnational Family Talks: An Autoethnographic Study - Muhammad Alasmari (Children, 2023)
Studies in Family Language Policy (FLP) have focused more on language patterns and practices in transnational families with little attention to the challenges of multilingualism. Through exploring diverse experiences in dealing with multilingualism, more can be understood about parent language ideology, the enactment of FLP, and factors related to identity construction. Therefore, the study highlights how the family experiences affect the way individual family members perceive social relations and social structures and how they construct and present their own identities. The study is based on an analysis of longitudinal data from children’s family transnational experiences and how the dynamic of FLP affected not only family talk style but also identity construction. The main focus of the study entails an analysis of personal auto-ethnographic accounts. The study explored the emergence of religious identity in the family talks via (1) using referring expressions to talk about religious places related to two different contexts, and (2) frequently using religious phrases in different settings, which, in turn, reveal the interplay between macro and micro factors affecting the parental language ideology, language planning, and identity construction in the FLP. This study contributed to the field of language policy by presenting the different trajectories in identity construction and family language in a transnational families from a less explored religious and ethnic group.